2021
DOI: 10.1002/jsfa.11147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of re‐ensiling on the fermentation quality and microbial community of napier grass (Pennisetum purpureum) silage

Abstract: BACKGROUND With the rapid development of animal husbandry, the silage trade has increased in frequency. The re‐ensiling of materials is often required before or after trading, resulting in the exposure of the silage to air before re‐sealing. To develop a re‐ensiling technique for silage, different silage exposure periods were simulated to check the possible effects on the fermentation quality and microbial community of silage. RESULTS Fresh and wilted napier grass (Pennisetum purpureum) were ensiled for 90 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…The most abundant phylum in MFM and PMFM was Proteobacteria, in agreement with Yuan et al 13 . and Yin et al 35 However, in AMFM, Firmicutes was found to be the most abundant phylum, reflecting the different abilities of Proteobacteria and Firmicutes to survive and multiply during the day and night. On the genus level, LAB genera represent only a small fraction of epiphytic microbiota.…”
Section: Discussionsupporting
confidence: 88%
“…The most abundant phylum in MFM and PMFM was Proteobacteria, in agreement with Yuan et al 13 . and Yin et al 35 However, in AMFM, Firmicutes was found to be the most abundant phylum, reflecting the different abilities of Proteobacteria and Firmicutes to survive and multiply during the day and night. On the genus level, LAB genera represent only a small fraction of epiphytic microbiota.…”
Section: Discussionsupporting
confidence: 88%
“…A lower relative abundance of Erwinia in total mixed ration silage was associated with the improved silage quality ( Jiang et al, 2020 ), as this genus belongs to Enterobacteria , which can compete with LAB for substrate. Both Paenibacillus and Psychrobacillus may promote growth of less acid-tolerant spoilage microorganisms; they were detected in Napier grass silage and mixed corn and soybean silage ( Zeng et al, 2020 ; Yin et al, 2021 ). Furthermore, Carnobacterium apparently decreased fermentation quality of Italian ryegrass silage ( Yan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Weissella and Pantoea were the dominant genera in Napier grass in Malaysia (Hisham et al, 2022 ). Interestingly, Weissella and Lactobacilli were the dominant genera in Napier grass silages from different regions, and LAB inoculants or wilting treatments regulated the structure of microbial communities (Hisham et al, 2022 ; Yin et al, 2021 ; Zi et al, 2021 ).…”
Section: Lactic Acid Bacteria Modulating Microbial Community Structur...mentioning
confidence: 99%